Mentorship Challenges: Reflections from Mentor-Teachers in Pre-Service Teacher Programs - Mkhomi, Moses Sipho; Mokobane, Z; Gqeba, NG; Mhlanga, N (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
Mentorship is crucial to pre-service teacher education, bridging the gap between theoretical knowledge and practical classroom experience. However, while extensive research has explored the perspectives of pre-service teachers (PSTs), limited attention has been given to mentor-teachers' challenges. This study examines the mentorship challenges encountered by mentor-teachers, framed within the Self-Regulation Learning (SRL) theory, which consists of three phases: Forethought, Performance, and Self-Reflection. Data were collected through semi-structured interviews with ten mentor-teachers from Buffalo City Metropolitan Education District schools using a qualitative phenomenological approach. Findings reveal three key challenges. First, in the forethought phase, PSTs lack structured preparation and clear expectations, leading to passive engagement and reliance on mentor-teachers. Second, in the performance phase, PSTs struggle with classroom execution and adaptability, failing to monitor and adjust their teaching strategies effectively. Third, in the self-reflection phase, many PSTs resist feedback and fail to engage in critical self-assessment, limiting their professional growth. This study recommends structured pre-placement training for PSTs, improved university-mentor communication, and the integration of reflection-based learning tools to enhance mentorship effectiveness. Strengthening mentorship programs through self-regulated learning strategies will better prepare PSTs for teaching challenges, promote autonomous learning, and reduce mentor-teacher burdens. This study contributes to teacher education literature by highlighting mentorship gaps and proposing a structured approach to improving mentorship in pre-service teacher training.